A dual-band laser filter film system and a preparation method thereof
Patent Information
- Application Number
- CN202611210806.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]本发明的目的旨在提出一种双波段激光滤光膜系及其制备方法,以解决现有技术不能达到最佳反射带宽和薄膜制备难度及成本偏高的技术问题
本发明提出的双波段激光滤光膜系制备方法具有制备难度小且成本低,能达到最佳反射带宽的优点,且本发明制备的双波段激光滤光膜系能够满足入射角度46°,光谱波段1.55μm±0.02μm范围内,反射率大于95%,光谱波段1.064μm±0.02μm范围内,透射率大于95%的光谱特性要求。
Smart Images

Figure CN122923149A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of dual-band laser filter film preparation technology, specifically relating to a dual-band laser filter film system and its preparation method. Background Technology
[0002] Light is a transverse wave, with its electric field vibration direction perpendicular to its propagation direction. The vibration direction of natural light is random. When light is incident on an optical interface at a non-perpendicular angle, its response to p-polarized light (vibration direction parallel to the incident plane) and s-polarized light (vibration direction perpendicular to the incident plane) is different. This leads to changes in the polarization state of the transmitted and reflected beams, and the larger the incident angle, the more significant this change. In filter systems, when light is incident at a large angle, the reflection bandwidth of s-polarized light is much larger than that of p-polarized light. Thus, the average reflection bandwidth of the spectrum often depends on the reflection bandwidth of p-polarized light. In laser applications, the wider the reflection bandwidth, the wider the range of laser angles that can be applied. In film system design, a wider reflection bandwidth provides a larger margin to cover the reflection band bandwidth required by customer technology, making film fabrication easier and increasing the yield rate. Therefore, it is necessary to study methods to extend the reflection bandwidth of p-polarized light at large angles to extend the average reflection bandwidth of the spectrum.
[0003] Currently, the common practice both domestically and internationally is to directly select the highest and lowest refractive index film materials from the material library for matching to extend the average reflection bandwidth. However, this method sometimes fails to achieve the optimal reflection bandwidth. In some cases, in order to extend the reflection bandwidth by a few nanometers to improve the spectral performance of optical components, the number and thickness of film layers are often increased by more than double, which greatly increases the difficulty and cost of thin film preparation. Summary of the Invention
[0004] The purpose of this invention is to propose a dual-band laser filter film system and its preparation method to solve the technical problems of existing technologies not being able to achieve optimal reflection bandwidth and the difficulty and high cost of thin film preparation.
[0005] This invention calculates the material refractive index matching value by taking advantage of the extreme value condition of the p-polarized light reflection bandwidth at large angles, thereby expanding the reflection bandwidth of the film system. The matching refractive index can be selected from an approximate refractive index in a material library, or it can be achieved by sputtering a mixture of high and low refractive index materials in a vacuum coating machine. The prepared dual-band laser filter film system can meet the spectral characteristics requirements of reflectivity greater than 95% within the spectral band of 1.55μm±0.02μm and transmittance greater than 95% within the spectral band of 1.064μm±0.02μm at an incident angle of 46°.
[0006] Based on one aspect of the present invention, this application proposes a method for preparing a dual-band laser filter film system, comprising the following steps: S1. Select optical substrate materials and make preliminary selections for film materials. The optical glass and film materials selected for laser detection devices are highly transparent and non-absorbent in the response spectrum band, and these optical glass and film materials have advantages such as strong mechanical properties and excellent environmental adaptability. S2. Calculate the extreme value condition of the reflection bandwidth of p-polarized light, and select the refractive index material that maximizes the reflection bandwidth of p-polarized light; S21. Define the correlation coefficient of p-polarized light reflection bandwidth. The calculation process is as follows: When incident at large angles, the effective refractive indices of p-polarized and s-polarized light in the film material are: (1) (2) Where n is the refractive index of the material, and θ is the angle of light propagation (or refraction) in the material. p n is the effective refractive index of p-polarized light. s is the effective refractive index of s-polarized light.
[0007] At large angles, the polarization reflection bandwidth in a film system is related to the ratio of the refractive index to the polarization index. The greater the difference in the refractive index ratio, the wider the reflection bandwidth. Therefore, at large angles, the refractive index in the film system is n. 1、 The reflection bandwidth of p-polarized light from the two materials of n2 is:
[0008] The reflection bandwidth of s-polarized light is:
[0009] The ratio of the reflection bandwidth of p-polarized light to that of s-polarized light is determined by the ratio of the refractive indices of p-polarized light to that of s-polarized light, μ; let... (3) Substituting the law of refraction: ,get: (4) That is, the ratio of the reflection bandwidth of p-polarized light to that of s-polarized light is less than 1. Therefore, at large angles, the average reflection bandwidth of the film system is mainly determined by the reflection bandwidth of p-polarized light.
[0010] Since the reflection bandwidth of p-polarized light is related to the ratio of its refractive index to its refractive index, the greater the difference in the refractive index ratio, the wider the reflection bandwidth. Therefore, the reflection bandwidth of p-polarized light is determined by its refractive index ratio coefficient. Decide; Substituting the law of refraction: ,get: (5) (6) therefore The smaller or greater the value of P-polarized light, the wider the reflection bandwidth; when the value is equal to 1, the reflection bandwidth of P-polarized light is the narrowest.
[0011] S22. Calculation of the extreme value condition for the reflection bandwidth of p-polarized light: Since the refractive indices of materials n1 and n2 are greater than 1, when n2, Given, let
[0012]
[0013] (7) The conclusion is (8) When n2, It is known that When the bandwidth is minimized, the formula for calculating the refractive index value that minimizes the bandwidth is: (9) when As can be seen from equation (9), there are two refractive index values that minimize the bandwidth. Between these two refractive index values, there is a refractive index value that maximizes the bandwidth. The material refractive index is searched for on both sides of the two refractive index values that minimize the bandwidth. The more the material refractive index is deviated from the two refractive index values that minimize the bandwidth, the wider the bandwidth of the p-polarized light formed. The material refractive index is compared with the refractive index value that maximizes the bandwidth between the two refractive index values that minimize the bandwidth, so as to select the refractive index material that maximizes the bandwidth of p-polarized light reflection. When n2, It is known that hour, If the bandwidth is at its maximum, then the formula for calculating the refractive index value that maximizes the bandwidth between the two refractive index values that minimize the bandwidth is as follows: (10) Right now
[0014] when hour, As can be seen from equation (9), the refractive index of the material can only be found by epitaxy on both sides of the refractive index that minimizes the bandwidth. The more the refractive index of the material on both sides deviates from the refractive index value that minimizes the bandwidth, the wider the bandwidth of the p-polarized light formed. The refractive indices of the materials found are compared, and the refractive index material that maximizes the bandwidth of the p-polarized light reflection is selected.
[0015] S3. Based on the spectral characteristic parameters, design the film structure and thickness, and perform vacuum deposition on the optical substrate material to obtain the coated optical substrate material; S4. The coated surface of the coated optical substrate material and the adhesive surface of the uncoated optical substrate material are bonded together using an adhesive layer material to obtain the dual-band laser filter system.
[0016] Preferably, in step S1, the optical substrate material is selected as a prism blank material made of H-K9L crown optical glass, with an angular accuracy of ±10″ and a refractive index of 1.52 at a spectral band of 1.55μm.
[0017] Preferably, in step S1, the initially selected film materials are TiO2 and SiO2, both with a purity of 99.99% or higher, and the refractive indices of TiO2 and SiO2 at a spectral band of 1.55 μm are 2.1 and 1.45, respectively.
[0018] Preferably, when the maximum refractive index value of the p-polarized light reflection bandwidth calculated in step S2 does not have a suitable approximate refractive index from the material library, it is achieved by sputtering a mixture of high and low refractive index materials in a vacuum coating machine; The formula for calculating the maximum refractive index value of the p-polarized light reflection bandwidth using sputtering with a mixture of high and low refractive index materials is as follows: (11) (12) Equivalent refractive index of the mixed evaporation material; , The refractive indices of the high- and low-refractive-index materials in the mixed evaporation material; , The volume ratio of high- and low-refractive-index materials in a mixed evaporation material.
[0019] Preferably, in step S3, titanium targets and silicon targets with a purity greater than 99.99% are selected for vacuum coating.
[0020] Vacuum coating machines can be used for thermal evaporation, ion source-assisted evaporation, ion beam sputtering, magnetron sputtering, etc. Preferably, in step S3, vacuum coating uses magnetron sputtering, and the specific operation steps are as follows: S31. When the vacuum degree of the magnetron sputtering coating machine reaches 6×10 -2 Pa~9×10 -2 At Pa, the optical substrate material is baked at 200℃ and kept at that temperature for 30-40 minutes, and then vacuum is continued. S32. When the vacuum degree reaches 2×10 -3 Pa~3×10 -3 Titanium dioxide was prepared by sputtering a titanium target with a purity greater than 99.99% at Pa, with an argon flow rate of 70 sccm, an oxygen flow rate of 35 sccm, a titanium target sputtering power of 150 W, and a sputtering rate of 0.2 nm / s. S33. Under the conditions of argon flow rate of 65 sccm, oxygen flow rate of 30 sccm, titanium target sputtering power of 20 W, silicon target sputtering power of 110 W, and co-sputtering rate of 0.25 nm / s, a mixed evaporation material with a refractive index of 1.546 was prepared by co-sputtering titanium target with a purity greater than 99.99% and silicon target with a purity greater than 99.99%. S34. Sputter the material of each film layer sequentially according to the designed film system structure and thickness. After preparation is completed, turn off the power and cool the equipment.
[0021] Preferably, in step S4, the adhesive layer material is an epoxy resin adhesive with a refractive index of 1.52 at a spectral wavelength of 1.55 μm. Using an epoxy resin adhesive with a refractive index of 1.52 ensures that the refractive index matches that of the optical glass. The adhesive layer thickness is 0.015 ± 0.005 mm, and it does not participate in thin-film interference. This epoxy resin adhesive is a highly transparent, non-absorbent adhesive layer material in the application wavelength range, characterized by high bonding strength and low shrinkage.
[0022] Based on another aspect of the present invention, a dual-band laser filter film system is proposed, which is prepared by the above-described preparation method. The film structure and film thickness of the dual-band laser filter film system are as follows: Glass / 243nm (TiO2) 346.3nm (M) 204.3nm (TiO2) 348.8nm (M) 223.94nm (TiO2) 360.4nm (M) 214.5nm (TiO2) 353.5nm (M) 215.6nm (TiO2) 351.6nm (M) ) 217.1nm (TiO2) 362.1nm (M) 217nm (TiO2) 348.7nm (M) 214nm (TiO2) 359nm (M) 219nm (TiO2) 354nm (M) 215.4nm (TiO2) 354.3nm (M) 215.4nm (TiO2) 3 54.7nm (M) 219.2nm (TiO2) 357.8nm (M) 213.6nm (TiO2) 349.6nm (M) 217.6nm (TiO2) 361.6nm (M) 216.5nm (TiO2) 351.6nm (M) 215.6nm (TiO2) 353.8 nm (M) 215.2nm (TiO2) 361.1nm (M) 222.2nm (TiO2) 347.6nm (M) 205.7nm (TiO2) 351.1nm (M) 239.9nm (TiO2) 195nm (M) 0.015±0.005mm (glue layer) / Glass; The M layer is a mixture of TiO2 and SiO2, and the volume ratio of TiO2 to SiO2 in the mixture is 48:277.
[0023] Preferably, the dual-band laser filter film has a reflectivity greater than 95% within an incident angle of 46° and a spectral band of 1.55μm±0.02μm, and a transmittance greater than 95% within a spectral band of 1.064μm±0.02μm.
[0024] Compared with the prior art, the present invention has the following technical effects: The dual-band laser filter film system preparation method proposed in this invention has the advantages of low preparation difficulty and low cost, and can achieve the optimal reflection bandwidth. Moreover, the dual-band laser filter film system prepared by this invention can meet the spectral characteristics requirements of reflectivity greater than 95% within the spectral band of 1.55μm±0.02μm and transmittance greater than 95% within the spectral band of 1.064μm±0.02μm at an incident angle of 46°. Attached Figure Description
[0025] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0026] Figure 1 This is a process flow diagram of the present invention in the embodiments; Figure 2This is a diagram of the film structure of the present invention in the embodiment; Figure 3 This is a schematic diagram illustrating the principle of magnetron sputtering of the present invention in an embodiment; Figure 4 This is a schematic diagram showing the placement of the F2000 collimator, adjustable turntable, and F1000 front mirror during the bonding process of the present invention in this embodiment. Figure 5 This is a schematic diagram showing the center of the F2000 collimator and the center of the F1000 front lens reticle coinciding during the bonding process of the present invention in an embodiment. Figure 6 This is a schematic diagram of the optical path during the bonding process of filter prism A and filter prism B in the embodiment of the present invention; Figure 7 This is a schematic diagram showing that during the bonding process of the present invention, the image emitted from the F1000 front mirror is reflected from the surface of the filter prism A and the collimated image A is located at the center of the reticle. The angular value reading between the image B emitted from the F2000 collimator and the center of the F1000 front mirror reticle after passing through the bonding filter prism (A / B) is less than 10″. Figure 8 This is a transmittance spectrum curve of the dual-band laser filter film system of the present invention in the embodiment; Figure 9 The image shows the reflectance spectrum of the dual-band laser filter film system of the product in the example. Detailed Implementation
[0027] The present invention will now be clearly described with reference to the accompanying drawings and specific embodiments. This description is merely illustrative and is not intended to limit the scope of the invention. Any modifications, equivalent substitutions, or improvements made by those skilled in the art based on the embodiments of the present invention without inventive effort to obtain all other embodiments should be included within the scope of protection of the present invention.
[0028] Example like Figure 2 As shown, this embodiment proposes a dual-band laser filter film system, the film structure and film thickness of which are as follows: Glass / 243nm (TiO2) 346.3nm (M) 204.3nm (TiO2) 348.8nm (M) 223.94nm (TiO2) 360.4nm (M) 214.5nm (TiO2) 353.5nm (M) 215.6nm (TiO2) 351.6nm (M) ) 217.1nm (TiO2) 362.1nm (M) 217nm (TiO2) 348.7nm (M) 214nm (TiO2) 359nm (M) 219nm (TiO2) 354nm (M) 215.4nm (TiO2) 354.3nm (M) 215.4nm (TiO2) 3 54.7nm (M) 219.2nm (TiO2) 357.8nm (M) 213.6nm (TiO2) 349.6nm (M) 217.6nm (TiO2) 361.6nm (M) 216.5nm (TiO2) 351.6nm (M) 215.6nm (TiO2) 353.8 nm (M) 215.2nm (TiO2) 361.1nm (M) 222.2nm (TiO2) 347.6nm (M) 205.7nm (TiO2) 351.1nm (M) 239.9nm (TiO2) 195nm (M) 0.015±0.005mm (glue layer) / Glass; The M layer is a mixture of TiO2 and SiO2, with a volume ratio of TiO2 to SiO2 of 48:277. The adhesive layer uses epoxy resin adhesive with a refractive index of 1.52 at a spectral wavelength of 1.55μm.
[0029] The optical thin film materials selected in this application are TiO2 and SiO2, both with a purity of over 99.99%. When used in laser detection devices, they possess advantages such as high transparency in the response spectrum, no absorption, high chemical stability, strong mechanical properties, and excellent environmental adaptability. Furthermore, the refractive indices of TiO2 and SiO2 materials at 1.55 μm are 2.1 and 1.45, respectively.
[0030] The adhesive layer material uses epoxy resin with a refractive index of 1.52, which matches the refractive index of the optical glass. The adhesive layer thickness is 0.015±0.005mm, and it does not participate in thin-film interference. This epoxy resin is a highly transparent, non-absorbent adhesive layer material in the application wavelength range, and features high bonding strength and low shrinkage.
[0031] Specifically, the optical substrate material of the dual-band laser filter film system is a prism blank material made of H-K9L crown optical glass, and the angular accuracy of the prism blank material is ±10″, with a refractive index of 1.52 at 1.55μm in the spectral band.
[0032] In this embodiment, the dual-band laser filter film has a reflectivity greater than 95% within an incident angle of 46° and a spectral band of 1.55μm±0.02μm, and a transmittance greater than 95% within a spectral band of 1.064μm±0.02μm.
[0033] For another purpose of the present invention, such as Figure 1 As shown, this application also proposes a method for fabricating the above-mentioned dual-band laser filter film system, comprising the following steps: S1. Define the correlation coefficient of p-polarized light reflection bandwidth. The calculation process is as follows: When incident at large angles, the effective refractive indices of p-polarized and s-polarized light in the film material are: (1) (2) Where n is the refractive index of the material, and θ is the angle of light propagation (or refraction) in the material. p n is the effective refractive index of p-polarized light. s is the effective refractive index of s-polarized light.
[0034] At large angles, the polarization reflection bandwidth in a film system is related to the ratio of the refractive index to the polarization index. The greater the difference in the refractive index ratio, the wider the reflection bandwidth. Therefore, at large angles, the refractive index in the film system is n. 1、 The reflection bandwidth of p-polarized light from the two materials of n2 is:
[0035] The reflection bandwidth of s-polarized light is:
[0036] The ratio of the reflection bandwidth of p-polarized light to that of s-polarized light is determined by the ratio of the refractive indices of p-polarized light to that of s-polarized light, μ; let... (3) Substituting the law of refraction: ,get: (4) That is, the ratio of the reflection bandwidth of p-polarized light to that of s-polarized light is less than 1. Therefore, at large angles, the average reflection bandwidth of the film system is mainly determined by the reflection bandwidth of p-polarized light.
[0037] Since the reflection bandwidth of p-polarized light is related to the ratio of its refractive index to its refractive index, the greater the difference in the refractive index ratio, the wider the reflection bandwidth. Therefore, the reflection bandwidth of p-polarized light is determined by its refractive index ratio coefficient. Decide; Substituting the law of refraction: ,get: (5) (6) therefore The smaller or greater the value of P-polarized light, the wider the reflection bandwidth; when the value is equal to 1, the reflection bandwidth of P-polarized light is the narrowest.
[0038] S2. Calculation of the extreme value condition for the reflection bandwidth of p-polarized light: Since the refractive indices of materials n1 and n2 are greater than 1, when n2, Given, let
[0039]
[0040] (7) The conclusion is (8) When n2, It is known that When the bandwidth is minimized, the formula for calculating the refractive index value that minimizes the bandwidth is: (9) when As can be seen from equation (9), there are two refractive index values that minimize the bandwidth. Between these two refractive index values, there is a refractive index value that maximizes the bandwidth. The material refractive index is searched for on both sides of the two refractive index values that minimize the bandwidth. The more the material refractive index is deviated from the two refractive index values that minimize the bandwidth, the wider the bandwidth of the p-polarized light formed. The material refractive index is compared with the refractive index value that maximizes the bandwidth between the two refractive index values that minimize the bandwidth, so as to select the refractive index material that maximizes the bandwidth of p-polarized light reflection. When n2, It is known that hour, If the bandwidth is at its maximum, then the formula for calculating the refractive index value that maximizes the bandwidth between the two refractive index values that minimize the bandwidth is as follows: (10) Right now
[0041] when hour, As can be seen from equation (9), the refractive index of the material can only be found by epitaxy on both sides of the refractive index that minimizes the bandwidth. The more the refractive index of the material on both sides deviates from the refractive index value that minimizes the bandwidth, the wider the bandwidth of the p-polarized light formed. The refractive indices of the materials found are compared, and the refractive index material that maximizes the bandwidth of the p-polarized light reflection is selected. When the calculated maximum refractive index value of p-polarized light reflection bandwidth does not have a suitable approximate refractive index from the material library, it is achieved by sputtering a mixture of high and low refractive index materials in a vacuum coating machine. The formula for calculating the maximum refractive index value of the p-polarized light reflection bandwidth obtained in step S2 is as follows: This is achieved using a mixture of high- and low-refractive-index materials through sputtering. (11) (12) Equivalent refractive index of the mixed evaporation material; , The refractive indices of the high- and low-refractive-index materials in the mixed evaporation material; , The volume ratio of high- and low-refractive-index materials in a mixed evaporation material.
[0042] In this embodiment, when TiO2 material is selected for calculation, then The refractive index of the prism blank material angle of incidence 46°; Substituting the law of refraction:
[0043] Calculations show that
[0044] If the bandwidth is at its maximum, then
[0045]
[0046] If the bandwidth is minimum, then
[0047] or
[0048] Analysis of the calculation results shows that there are no better refractive index materials in the material library between refractive indices greater than 2.1 and less than 1.26. Between these two refractive indices, 1.546 is the material with the largest bandwidth. SiO2 with a refractive index of 1.46 and Al2O3 with a refractive index of 1.66 are already the best materials in the library, but they are still significantly different from 1.546. A refractive index of 1.546 should be achieved through the evaporation of a mixture of high and low refractive indices. According to formulas (11) and (12), the volume ratio of TiO2 to SiO2 in the mixture is 48:277.
[0049] Based on formula (5), the bandwidth comparison of P-polarized light is calculated as follows: TiO2 and materials with a refractive index of 1.546 are matched.
[0050] TiO2 and SiO2 are matched. According to the law of refraction, the refraction angle of SiO2 is...
[0051]
[0052] TiO 2与 Al2O3 matching, according to the law of refraction, the refraction angle of Al2O3
[0053]
[0054] Therefore, titanium dioxide (TiO2) has a large p-polarized light reflection bandwidth when matched with a material with a refractive index of 1.546.
[0055] In this embodiment, when SiO2 material is selected for calculation, then The refractive index of the prism blank material angle of incidence 46°; Substituting the law of refraction:
[0056] Calculations show that
[0057] If the bandwidth is at its maximum, then
[0058]
[0059] If the bandwidth is minimum, then
[0060] or
[0061] Analysis and calculation results show that for refractive indices greater than 1.665, TiO2 material with a refractive index of 2.1 can be selected, and for refractive indices less than 1.45, MgF2 material with a refractive index of 1.38 can be selected.
[0062] Matching TiO2 with SiO2, MgF2 with SiO2, and a material with a refractive index of 1.546 with SiO2, and performing p-polarized light bandwidth analysis on these three refractive index matches, according to formula (5): Materials with a refractive index of 1.546 are well-matched with SiO2:
[0063] TiO2 and SiO2 are matched:
[0064] MgF2 and SiO2 are well-matched: According to the law of refraction, the angle of refraction of MgF2 is... ;
[0065] Therefore, TiO2 and SiO2 have a large p-polarized light reflection bandwidth when matched.
[0066] In summary, the extreme values of the p-polarized light reflection bands of the two materials were calculated, and a material with a refractive index of 1.546 was achieved by mixing high and low refractive indices and evaporating it. This material was then matched with TiO2 for film design. According to formulas (11) and (12), the volume ratio of TiO2 to SiO2 in the mixture of TiO2 and SiO2 is 48:277.
[0067] S3. A vacuum coating method is used to obtain a coated prism blank on a selected prism blank material; Specifically, titanium and silicon targets with a purity greater than 99.99% are selected for vacuum coating.
[0068] Vacuum coating machines can use thermal evaporation, ion source-assisted evaporation, ion beam sputtering, magnetron sputtering, etc. Preferably, in step S4, vacuum coating uses magnetron sputtering (e.g., Figure 3 (As shown), the specific operation steps are as follows: S41. When the vacuum degree of the magnetron sputtering coating machine reaches 6×10 -2 Pa~9×10 -2 At Pa, the optical substrate material is baked at 200℃ and kept at that temperature for 30-40 minutes, and then vacuum is continued. S42. When the vacuum degree reaches 2×10 -3 Pa~3×10 -3Titanium dioxide was prepared by sputtering a titanium target with a purity greater than 99.99% at Pa, with an argon flow rate of 70 sccm, an oxygen flow rate of 35 sccm, a titanium target sputtering power of 150 W, and a sputtering rate of 0.2 nm / s. S43. Under the conditions of argon flow rate of 65 sccm, oxygen flow rate of 30 sccm, titanium target sputtering power of 20 W, silicon target sputtering power of 110 W, and co-sputtering rate of 0.25 nm / s, a mixed evaporation material with a refractive index of 1.546 was prepared by co-sputtering titanium target with a purity greater than 99.99% and silicon target with a purity greater than 99.99%. S44. Sputter the material of each film layer sequentially according to the designed film system structure and thickness. After preparation is completed, turn off the power and cool the equipment.
[0069] Baking and maintaining a constant temperature on optical material substrates helps improve the adhesion of film formation on the substrate surface.
[0070] The main process parameters for the magnetron sputtering film in the above steps are shown in Table 1 below: Table 1 Main process parameters of magnetron sputtering film
[0071] S4. Bond the coated surface of the coated prism blank to the adhesive surface of another selected prism blank material to obtain the dual-band laser filter film system.
[0072] Specifically, the coated prism blank is named filter prism A, and the other prism blank to be bonded is named filter prism B, such as... Figure 4-7 As shown, the specific process of gluing is as follows: (1) Adjust the position of the F1000 front lens so that the image emitted from the F2000 collimator coincides with the center of the reticle of the F1000 front lens; (2) Place the adhesive surface of filter prism A horizontally on a Class 100 cleanroom workbench using a special tooling. On the cleanroom workbench, drip epoxy resin onto the adhesive surface of the prism. Press the adhesive surface of filter prism B horizontally onto it and gently squeeze to remove the glue, ensuring that there are no air bubbles, dust, impurities, etc. on the adhesive surface and in the adhesive layer. During the glue removal process, measure the thickness of the parts with a micrometer and control the thickness of the adhesive layer to 0.015±0.005mm. Place the glued filter prisms (A / B) on the instrument's adjustable rotating stage. (3) Adjust the adjustable turntable so that the image emitted from the F1000 front mirror is reflected from the surface of the filter prism A and the autocollimated image A is located at the center of the reticle. The image emitted from the F2000 collimator B is located at the center of the reticle of the F1000 front mirror after passing through the cemented filter prism (A / B) (or the angular value reading between its position and the center of the reticle is less than 10″). After standing for 12 hours, the adhesive layer is initially cured. Then, place the cemented filter prism (A, B) into an oven and bake at a temperature of 50℃~60℃ for 5~6 hours to allow the adhesive layer to fully cure.
[0073] like Figure 8 , Figure 9 As shown, the spectral characteristics of the dual-band laser filter film system obtained after bonding were tested, and the test results met the design requirements.
[0074] The working principle of this invention is as follows: by calculating the material refractive index matching value through the extreme value condition of p-polarized light reflection bandwidth at large angles, the reflection bandwidth of the film system is extended. The matching refractive index can be selected from an approximate refractive index from a material library, or it can be achieved by sputtering a mixture of high and low refractive index materials in a vacuum coating machine.
[0075] The embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A method for preparing a dual-band laser filter film system, characterized in that, Includes the following steps: S1. Select optical substrate materials and make preliminary selections for film materials. Select optical glass materials and film materials with high transparency and no absorption in the response spectrum band for laser detection devices; S2. Calculate the extreme value condition of the reflection bandwidth of p-polarized light, and select the refractive index material that maximizes the reflection bandwidth of p-polarized light; S21. Define the correlation coefficient of p-polarized light reflection bandwidth. The calculation formula is as follows: (Ⅰ) Wherein, n1 and n2 are the refractive indices of the high and low refractive index materials in the dual-band laser filter system, respectively; The angle of refraction of light in a material with a low refractive index; Since the reflection bandwidth of p-polarized light is related to the ratio of its refractive index to that of p-polarized light, the greater the difference in the refractive index ratio, the wider the reflection bandwidth. The smaller or greater the value of P-polarized light is than 1, the wider the bandwidth of P-polarized light reflection; when the value is equal to 1, the bandwidth of P-polarized light reflection is the narrowest. S22. Calculate the extreme value condition for the reflection bandwidth of p-polarized light: When n2, It is known that When the bandwidth is minimized, the formula for calculating the refractive index value that minimizes the bandwidth is: (Ⅱ) when As can be seen from equation (II), there are two refractive index values that minimize the bandwidth. Between these two refractive index values, there is a refractive index value that maximizes the bandwidth. The refractive index of the material is searched by extending outward from the two refractive index values that minimize the bandwidth. The more the refractive index of the material is deviated from the two refractive index values that minimize the bandwidth, the wider the bandwidth of the p-polarized light formed. The refractive index of the material is compared with the refractive index value that maximizes the bandwidth between the two refractive index values that minimize the bandwidth, so as to select the refractive index material that maximizes the bandwidth of p-polarized light reflection. when hour, If the bandwidth is at its maximum, then the formula for calculating the refractive index value that maximizes the bandwidth between the two refractive index values that minimize the bandwidth is as follows: (Ⅲ) Right now (Ⅳ) when hour, As can be seen from equation (II), the refractive index of the material can only be found by epitaxy on both sides of the refractive index that minimizes the bandwidth. The more the refractive index of the material on both sides deviates from the refractive index value that minimizes the bandwidth, the wider the bandwidth of the p-polarized light formed. The refractive indices of the materials found are compared, and the refractive index material that maximizes the bandwidth of p-polarized light reflection is selected. S3. Based on the spectral characteristic parameters, the film structure and thickness are designed, and vacuum coating is performed on the optical substrate material to obtain the coated optical substrate material; S4. The coated surface of the coated optical substrate material and the adhesive surface of the uncoated optical substrate material are bonded together using an adhesive layer material to obtain the dual-band laser filter system.
2. The preparation method according to claim 1, characterized in that, In step S1, the optical substrate material is selected as a prism blank material made of H-K9L crown optical glass, with an angular accuracy of ±10″ and a refractive index of 1.52 at a spectral band of 1.55μm.
3. The preparation method according to claim 1, characterized in that, In step S1, the initially selected film materials are TiO2 and SiO2, both with a purity of over 99.99%, and the refractive indices of TiO2 and SiO2 at a spectral band of 1.55 μm are 2.1 and 1.45, respectively.
4. The preparation method according to claim 1, characterized in that, When the maximum refractive index value of the p-polarized light reflection bandwidth calculated in step S2 is not available from the material library, it is achieved by sputtering a mixture of high and low refractive index materials in a vacuum coating machine. The formula for calculating the maximum refractive index value of the p-polarized light reflection bandwidth using sputtering with a mixture of high and low refractive index materials is as follows: (Ⅴ) (Ⅵ) Equivalent refractive index of the mixed evaporation material; , The refractive indices of the high- and low-refractive-index materials in the mixed evaporation material; , The volume ratio of high- and low-refractive-index materials in a mixed evaporation material.
5. The preparation method according to claim 1, characterized in that, In step S3, titanium and silicon targets with a purity greater than 99.99% are selected for vacuum coating.
6. The preparation method according to claim 5, characterized in that, In step S3, vacuum coating is performed using magnetron sputtering. The specific operation steps are as follows: S31. When the vacuum degree of the magnetron sputtering coating machine reaches 6×10 -2 Pa~9×10 -2 At Pa, the optical substrate material is baked at 200℃ and kept at that temperature for 30 min to 40 min, and then vacuum is continued. S32. When the vacuum degree reaches 2×10 -3 Pa~3×10 -3 At Pa, titanium dioxide was prepared by sputtering a titanium target with a purity greater than 99.99% under the conditions of argon flow rate of 70 sccm, oxygen flow rate of 35 sccm, titanium target sputtering power of 150 W, and sputtering rate of 0.2 nm / s. S33. Under the conditions of argon flow rate of 65 sccm, oxygen flow rate of 30 sccm, titanium target sputtering power of 20 W, silicon target sputtering power of 110 W, and co-sputtering rate of 0.25 nm / s, a mixed evaporation material with a refractive index of 1.546 was prepared by co-sputtering titanium target with a purity greater than 99.99% and silicon target with a purity greater than 99.99%. S34. Sputter the material of each film layer sequentially according to the designed film system structure and thickness. After preparation, turn off the power and cool the equipment.
7. The preparation method according to claim 1, characterized in that, In step S4, the adhesive layer material is an epoxy resin adhesive with a refractive index of 1.52 at a spectral wavelength of 1.55 μm.
8. A dual-band laser filter film system, characterized in that, The dual-band laser filter film system, prepared using the preparation method described in any one of claims 1-7, has the following film structure and thickness: Glass / 243nm (TiO2) 346.3nm (M) 204.3nm (TiO2) 348.8nm (M) 223.94nm (TiO2) 360.4nm (M) 214.5nm (TiO2) 353.5nm (M) 215.6nm (TiO2) 351.6nm (M) 217.1nm (TiO2) 362.1nm (M) 217nm (TiO2) 348.7nm (M) 214nm (TiO2) 359nm (M) 219nm (TiO2) 354nm (M) 215.4nm (TiO2) 354.3nm (M) 215.4nm (TiO2) 354.7 nm (M) 219.2nm (TiO2) 357.8nm (M) 213.6nm (TiO2) 349.6nm (M) 217.6nm (TiO2) 361.6nm ( M) 216.5nm (TiO2) 351.6nm (M) 215.6nm (TiO2) 353.8nm (M) 215.2nm (TiO2) 361.1nm (M) 22 2.2nm (TiO2) 347.6nm (M) 205.7nm (TiO2) 351.1nm (M) 239.9nm (TiO2) 195nm (M) 0.015±0.005mm (adhesive layer) / Glass; wherein layer M is a mixture of TiO2 and SiO2, and the volume ratio of TiO2 to SiO2 in the mixture of TiO2 and SiO2 is 48:
277.
9. A dual-band laser filter system according to claim 8, characterized in that: The dual-band laser filter system has a reflectivity greater than 95% within an incident angle of 46° and a spectral band of 1.55μm±0.02μm, and a transmittance greater than 95% within a spectral band of 1.064μm±0.02μm.